PENGARUH SUBSTITUSI TEPUNG SORGUM TERHADAP KARAKTERISTIK KIMIA, FISIKA, DAN ORGANOLEPTIK COOKIES DENGAN ALPUKAT SEBAGAI SUBSTITUSI LEMAK - Syifahaque, An-Nida; Siswanti, Siswanti; Atmaka, Windi (Universitas Sebelas Maret (UNS), 2022)
Cookies are one of the most popular snacks. In order to reduce imports of wheat, an alternative that can be done is replacing wheat flour with sorghum flour, a food that can be produced in Indonesia and have a function close to wheat. Sorghum flour is expected to increase the nutritional and functional value of cookies. To reduce the health risks of saturated fat in cookies, butter is substituted with avocado which contains unsaturated fat and has similar characteristics to butter. The aim of this study was to determine the influence of sorghum flour substitution to chemical, physical, and organoleptic characteristic of cookies, and to know the best cookie formulation. This study used a completely randomized design (CRD) with one factor that is variation in sorghum flour substitution. The formula is using 50% butter : 50% avocado with ratio of wheat flour and sorghum flour 5:0 (w/w); 4:1 (w/w); 3:2 (w/w); 2:3 (w/w); 1:4 (w/w). The data were analyzed using one way Anova and if it showed a significant difference, a further test was carried out with DMRT at α=5%. Cookies with the best and most preferred formula is cookies with ratio of wheat flour:sorghum flour 2:3 (w/w) that have chemical characteristics including water content 11.6%, ash content 2.44%, protein content 5.97%, fat content 13.87%, carbohydrate content 77.60%, total calories 4.38 kcal/g, antioxidant activity 50.24%; physical characteristics including hardness 157.23 N and spread ratio 4.60.